EFFECT OF LYSINE ON OXYGEN CONSUMPTION AND CHOLESTEROL CONTENTS OF RAT ADRENAL UNDER DIFFERENT ELECTROLYTE CONCENTRATIONS - JAIN, SUBODH KUMAR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1990)
In vitro studies on the oxygen consumption and cholesterol of mammalian adrenal under the influence of amino acid lysine shows that it stimulates the oxygen consumption and cholesterol contents. This behaviour the oxygen consumption and cholesterol contents change correspondingly.